Distinct abnormalities of small bowel and regional colonic volumes in subtypes of irritable bowel syndrome revealed by MRI - Lam, Ching; Chaddock, Gemma; Marciani Laurea, Luca; Costigan, Carolyn; Cox, Eleanor; Hoad, Caroline; Pritchard, Susan E.; Gowland, Penny A.; Spiller, Robin C. (Nature Publishing Group, 2016)
OBJECTIVES: Non-invasive biomarkers which identify different mechanisms of disease in subgroups of irritable bowel syndrome (IBS) could be valuable. Our aim was to seek useful magnetic resonance imaging (MRI) parameters that could distinguish each IBS subtypes. METHODS: 34 healthy volunteers (HV), 30 IBS with diarrhea (IBS-D), 16 IBS with constipation (IBS-C), and 11 IBS with mixed bowel habit (IBS-M) underwent whole-gut transit and small and large bowel volumes assessment with MRI scans from t=0 to t=360 min. Since the bowel frequency for IBS-M were similar to IBS-D, IBS-M and IBS-D were grouped together and labeled as IBS non-constipation group (IBS-nonC). RESULTS: Median (interquartile range): fasting small bowel water content in IBS-nonC was 21 (10–42), significantly less than HV at 44 ml (15–70), P<0.01 as was the postprandial area under the curve (AUC) P<0.01. The fasting transverse colon volumes in IBS-C were significantly larger at 253 (200–329) compared with HV, IBS-nonC whose values were 165 (117–255) and 198 (106–270) ml, respectively, P=0.02. Whole-gut transit time for IBS-C was prolonged at 69 (51–111), compared with HV at 34 (4–63) and IBS-D at 34 (17–78) h, P=0.03. Bloating score (VAS 0–10 cm) correlated with transverse colon volume at t=405 min, Spearman r=0.21, P=0.04. CONCLUSIONS: The constricted small bowel in IBS-nonC and the dilated transverse colon in IBS-C point to significant differences in underlying mechanisms of disease.